Rhizosphere biotechnology : plant growth, retrospect and prospect - Roy, A. K. (Awadh Kishore), 1950-; Chakraborty, B. N.; Mukadam, D. S.; Rashmi, Dr.; Tilka Manjhi Bhagalpur University. Dept. of Botany (Jodhpur : Scientific Publishers (India), 2007)
Contributed papers presented at a national symposium entitled'Rhizosphere biotechnology/microbs-retrospects and prospects' held on Nov. 29-30, 2004 at the University Dept. of Botany, T.M. Bhagalpur University, India.
PS Refined - Dr. Munir
Includes bibliographical references.
Keywords: Soil microbiology -- Congresses; Growth (Plants) -- Congresses; Rhizosphere -- Congresses